Efektivitas Penerapan Metode Cross Line Terhadap Pemahaman Konsep Perkalian Pada Siswa Kelas III SD Negeri 2 Baubau - Rismayani Armin; Nur Fauzia (Jurnal Akademik Pendidikan Matematika, 2026)
This research uses a quantitative approach with a quasi-experimental design. The population in this study were all class III students at SD Negeri 2 Baubau which consisted of 210 students. The sampling technique in this research used a purposive sampling technique, where one class was the experimental class which was given learning using the recitation method using worksheets, namely class VII.I and another class was the control class which was not given learning using the recitation method, namely class VII.2 which each class has 31 students so the sample used is 62 students. The research instrument used in this research is a test. The data collection technique in this research was carried out using tests in the form of essays which were given at the beginning and end of the lesson to the two sample groups to measure students' mastery of the material on rectangular shapes. The data obtained were analyzed using descriptive analysis and inferential analysis in the form of t-test. The results in this research are the analysis of normality and homogeneity tests showing that the data are normally distributed and homogeneous, followed by hypothesis testing estimated using a hypothesis test (independent sample T-Test) with equal variances assumed. Based on the analysis results, the calculated t-value= 3.327>t-table-2.009 with a significance level of 0.002 <0.05, so Ho is rejected and Hi is accepted based on the hypothesis acceptance criteria. Therefore, the researcher concludes that the application of the cross-line method is significantly effective in improving the understanding of multiplication concepts among third-grade students at SD Negeri 2 Baubau.